Functional characterization of COMT genes in Chinese white pear (Pyrus bretschneideri) and their role in lignin synthesis - Feng, Xiaofeng; Wu, Xianang; Hong, Jiayi; Guo, Zihui; Khan, Yasmin; Wei, Dongyi; Fan, Honghong; Cai, Yongping (Frontiers in Plant Science, 2025)
BackgroundCaffeic acid O-methyltransferase (COMT) is an S-adenosyl-L-methionine (SAM)-dependent O-methyltransferase that catalyzes the methylation of caffeic acid to form ferulic acid, a critical step in lignin biosynthesis. Lignin is essential for the development of stone cells in pear fruit, imparting their characteristic texture. Although COMT has been extensively studied in model organisms, its function in pears remains less explored.ResultsIn this study, we identified 29 COMT genes in the pear variety ‘Dangshan Su’, classified into five subfamilies. These genes exhibit five conserved motifs, and promoter analysis indicates potential hormonal regulation. Transcriptome data showed that PbrCOMT1 is the predominant COMT gene in ‘Dangshan Su’ fruit and is likely crucial for lignin synthesis. In situ hybridization revealed that the expression of PbrCOMT1 coincides with lignin, highlighting its role in stone cell development. Functional studies, including transient transformation of pear and strawberry fruit, as well as stable transformation of Arabidopsis thaliana, demonstrated that PbrCOMT1 overexpression enhances lignin content, while gene silencing diminishes it. Overexpression in Arabidopsis and fruit models resulted in growth inhibition, associating PbrCOMT1 with lignin-related developmental processes.ConclusionsOur findings indicate that PbrCOMT1 is a key gene involved in lignin synthesis and stone cell development in pear fruit. This provides a molecular basis for enhancing pear fruit quality through targeted genetic approaches.